A numerical investigation of preheated diluted oxidizer influence on NOx emission of biogas flameless combustion using Taguchi approach. (1st September 2018) - Mehregan, Mina; Moghiman, Mohammad
Abstract: The present investigation submits an analysis about the influence of preheated diluted oxidizer parameters on NOx emissions from a biogas flameless burner. The design parameters and their levels were diluting species, N2 and CO2, oxygen concentration of 5, 7 and 10% and preheated air temperature at 900, 1100 and 1300 K. An L18 (2 1  3 2 ) Taguchi orthogonal array was employed to design the test plan for numerical simulations. The results reveal that an increase in oxygen concentration leads to more NOx emissions. The same result is obtained by increasing preheated air temperature. Also, air dilution with N2 gives better result for reducing NOx emission compared to CO2 dilution method. As well as, according to the ANOVA (analysis of variance), the most effective design factors on NOx emission are oxygen concentration and then preheated air temperature with around 57% and 32% contribution, respectively, which indicates NOx emission can be successfully enhanced by controlling these parameters.